Pain management in children has significantly improved in the Italian emergency departments. (29th January 2020) - Benini, Franca; Castagno, Emanuele; Urbino, Antonio F.; Fossali, Emilio; Mancusi, Rossella Letizia; Milani, Gregorio P.
Abstract: Aim: Pain in children is often poorly assessed and treated in Italian emergency departments (EDs) as found in a survey conducted among the centres of the "Pain in Pediatric Emergency Room (PIPER)" Study Group in 2010. Our aim was to evaluate the changes in pain management in Italian EDs in the last years. Method: A structured questionnaire about pain assessment, protocols, use of local anaesthetics before venipuncture, opioids and adjuvants was mailed to 46 Italian EDs between November 2017 and April 2018. Results: Pain was always assessed at triage in 34 centres (73.9%). Algometric scales were used in over 90% of EDs. Triage protocols were available in 37 centres (80.4%). Local anaesthetics before venipuncture were always used in six centres (13.0%). Protocols included opioids and adjuvants in 73.0% and 47.2%, respectively. Triage pain assessment was always done in 91.0% of the centres joining the PIPER Study Group up to 2015 and 56.5% in ones that joined the Group after 2015 ( P = .017). Local anaesthetics before venipuncture were given in 39.1% of the centres joining until up to 2015 and 13.0% in ones that joined the Group after 2015 ( P = .003). Conclusion: Paediatric pain management has significantly improved in Italian EDs in the last 8 years. The centres joining the PIPER Study Group for longer time have shown better results for the indicators considered in the survey.